[Japan] (Tokyo, Japan, 1964)
This book is dedicated to that aim. For all visitors to the XVIII Olympiad, we trust that this book, by helping you to recall your pleasant days in Japan, will deepen your understanding of this modern country with its classic traditions and ancient culture.
Keywords: Japan,Japan,Japan; Description and travel,History,Socioeconomic conditions